Impact of electromagnetic fields on human vestibular system and standing balance: pilot results and future developments. Issue 1 (March 2016) - Allen, A; Villard, S; Corbacio, M; Goulet, D; Plante, M; Souques, M; Deschamps, F; Ostiguy, G; Lambrozo, J; Thomas, A W; Legros, A
Abstract: Although studies have found that extremely low-frequency (ELF, < 300 Hz) magnetic fields (MF) can modulate human standing balance, the acute effects of electromagnetic fields on standing balance have not been systematically investigated. This work aims to establish the threshold for acute standing balance modulation during ELFMF exposure. One hundred volunteers will be exposed to transcranial electric stimulations (Direct Current - DC and Alternating Current - AC, 1 mA) and ELFMF (0 to 160 Hz, 0 to 100 mT). The displacement of their center of pressure will be collected and analyzed as an indicator of vestibular performance. During pilot testing (n=6), we found increased lateral sway with DC, and to a lesser extent, AC exposure. The ELFMF exposure system still needs to be adapted to allow meaningful results. Future protocol design will test for possible effects due to exposures in the radiofrequency range (i.e. above 3 kHz). These results will contribute to the literature documenting exposure guidelines aiming to protect workers and the general public.